Click Reaction in the Synthesis of Dendrimer Drug-delivery Systems - García-Álvarez, Fernando; Martínez-García, Marcos (Current Medicinal Chemistry, 2022)
Drug delivery systems are designed for the targeted delivery and controlled release of medicinal agents. Among the materials employed as drug delivery systems, dendrimers have gained increasing interest in recent years because of their properties and structural characteristics. The use of dendrimer-nanocarrier formulations enhances the safety and bioavailability, increases the solubility in water, improves stability and pharmacokinetic profile, and enables efficient delivery of the target drug to a specific site. However, the synthesis of dendritic architectures through convergent or divergent methods has drawbacks and limitations that disrupt aspects related to design and construction, and consequently, slow down the transfer from academia to industry. In that sense, the implementation of click chemistry has received increasing attention in the last years, as it offers new efficient approaches to obtain dendritic species in good yields and higher monodispersity. This review focuses on recent strategies for building dendrimer drug delivery systems using click reactions from 2015 to early 2021. The dendritic structures showed in this review are based on β -cyclodextrins (β-CD), poly(amidoamine) (PAMAM), dendritic poly (lysine) (PLLD), dimethylolpropionic acid (bis-MPA), phosphoramidate (PAD), and poly(propargyl alcohol-4-mercaptobutyric (PPMA).
Keywords: Dendrimers